The Effect of the Allowance for Impairment Losses (CKPN) and Net Interest Margin (NIM) on Profitability, with Bank Size As a Moderating Variable, in Banks Listed on the Indonesian Stock Exchange (2021-2024) - Evriansyah, Evriansyah; Ulupui, I Gusti Ketut Agung; Musyaffi, Ayatulloh Michael (CV. Proaksara Global Transeduka, 2025)
The degree to which banks generate earnings stands as a consequential barometer of the enduring viability of financial intermediation and the robustness of the monetary ecosystem as a whole. Among Indonesian depository institutions, a discernible upswing in profitability has been charted in the post-pandemic era, corroborated by a successive appreciation in Return on Assets (ROA) throughout 2021 to 2024. Notwithstanding this affirmative trajectory, the governance of credit deterioration and the calibration of net interest revenue remain persistent impediments confronting the industry. Accordingly, this inquiry is undertaken to scrutinize the extent to which the Allowance for Impairment Losses (CKPN) and Net Interest Margin (NIM) exert bearing upon ROA, with a concomitant examination of whether institutional magnitude functions as a moderating variable within these nexuses, as observed across bourseenlisted banking entities in Indonesia spanning the quadrennial interval of 2021 through 2024. Secondary data culled from the annual and financial disclosures of banking institutions constitute the empirical bedrock of this inquiry. Panel data regression serves as the principal analytical apparatus, encompassing descriptive statistics, model adjudication protocols, namely the Chow and Hausman tests, and classical assumption diagnostics. Empirical evidence reveals that CKPN and NIM each exert a discernible bearing upon ROA. Of particular salience is the moderating comportment of institutional magnitude, which attenuates the influence of CKPN on ROA whilst concurrently amplifying that of NIM. These revelations underscore the imperativeness of judiciously equilibrating risk-contingent provisioning directives and interest margin stewardship, with due cognizance of bank scale, in perpetuating sustainable profitability.